2018
DOI: 10.3892/ol.2018.8602
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated genes targeted by microRNAs and metabolic pathways in bladder cancer revealed by bioinformatics methods

Abstract: The present study aimed to identify bladder cancer-associated microRNAs (miRNAs) and target genes, and further analyze the potential molecular mechanisms involved in bladder cancer. The mRNA and miRNA expression profiling dataset GSE40355 was downloaded from the Gene Expression Omnibus database. The Limma package in R was used to identify differential expression levels. The Human microRNA Disease Database was used to identify bladder cancer-associated miRNAs and Target prediction programs were used to screen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…CALM1 is composed of Ca 2+ -binding EF-hands, and participates in signaling pathways that modulates proliferation, motility and differentiation [ 14 ]. Several studies found that the expression level of CALM1 was markedly associates with many kinds of cancer, including bladder cancer [ 15 ], prostate cancer [ 16 ] and nasopharyngeal carcinoma [ 17 ]. As far as CALM is concerned, numerous investigations have been carried out on mechanistic aspects, mainly in the cell proliferation, programmed cell death and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…CALM1 is composed of Ca 2+ -binding EF-hands, and participates in signaling pathways that modulates proliferation, motility and differentiation [ 14 ]. Several studies found that the expression level of CALM1 was markedly associates with many kinds of cancer, including bladder cancer [ 15 ], prostate cancer [ 16 ] and nasopharyngeal carcinoma [ 17 ]. As far as CALM is concerned, numerous investigations have been carried out on mechanistic aspects, mainly in the cell proliferation, programmed cell death and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, many miRNAs have been found to be abnormally expressed in BC, playing a role in promoting or inhibiting tumors 3033. Abnormal expression in miRNA tumor tissues is reflected in two aspects: up-regulation and down-regulation.…”
Section: Discussionmentioning
confidence: 68%
“…CALM1 is composed of Ca 2+ -binding EF-hands, and participates in signaling pathways that modulates proliferation, motility and differentiation [14]. Several studies found that the expression level of CALM1 was markedly associates with many kinds of cancer, including bladder cancer [15], prostate cancer [16] and nasopharyngeal carcinoma [17]. As far as CALM is concerned, numerous investigations have been carried out on mechanistic aspects, mainly in the cell proliferation, programmed cell death and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we focus on CALM1. CALM is composed of Ca 2+ -binding EF-hands, and participates in signaling pathways that modulates proliferation, motility and differentiation [15]. Several studies found that the expression level of CALM1 was markedly associates with many kinds of cancer, including bladder cancer [16], prostate cancer [17] and nasopharyngeal carcinoma [18].…”
Section: Introductionmentioning
confidence: 99%